The Effect of Kangaroo Mother Care in Increasing Body Weight and Temperature in Premature Infants: Meta-Analysis - Pravitasari, Ines Ratni; Widyaningsih, Vitri; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Preterm birth is the leading cause of death in toddlers by 7.5% - 12.5% in various regions of the world. Premature is one of the causes of low birth weight and is a factor that increases the risk of hypothermia. Kangaroo Mother Care is a powerful and easy-to-use method for improving the long-term health and well-being of premature babies. This study aimed to estimate the average effect of Kangaroo Mother Care therapy on increasing body weight and temperature of premature infants.Subjects and Method: This was a meta-analysis and a systematic. The articles used were obtained from PubMed, Science Direct and Google Scholar. The inclusion criteria used were full text articles with the Randomized Control Trial (RCT) design, the study subjects were premature infants, the treatment provided was Kangaroo Mother Care with a comparison of conventional care, weight and temperature assessment of premature infants using stan